THE EFFECT OF FOOD QUALITY AND SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION AND REPURCHASE INTENTION (CASE STUDY OF HOT PLATE RESTAURANTS) - Hidayat, Desman; Bismo, Aryo; Basri, Amelia Ruwaida (Department of Management, 2020)
The food and beverages industry has been growing rapidly, making the competition in this industry higher. Therefore, innovation is needed to survive. The purpose of this study is to analyze the influence of Food Quality and Service Quality on the Customer Satisfaction of hot plate restaurants? consumers, which in turn will have an impact on Repurchase Intention. The method used in this study is a quantitative approach, using a Likert Scale as a measurement method. Data analysis uses the structural equation modeling (SEM) method with SmartPLS 3.0 tools. The population of this study is XYZ hot plate restaurants? consumers in Sunter and Bekasi, age 16-40 years old, with the status of students, employees, or entrepreneurs. Survey were done within 6 months on 2018 to 2019. The minimum sample needed for this research is 100 samples by using the Slovin formula. The results of this study show significant and positive effects, both individually and simultaneously, between Food Quality and Service Quality to Customer Satisfaction and its impact on Repurchase Intention. Therefore, in order to compete with others, XYZ hot plate restaurants should (1) Improve and maintain their foods and drinks, (2) Maintain their employees? credibility, and (3) Reduce the waiting list.